MICRO AND MACROECONOMIC DETERMINANTS OF THE FINANCIAL PERFORMANCE OF LIFE INSURANCE FIRMS IN INDONESIA: AN EMPIRICAL EVIDENCE - Toto Sugiharto (Universitas Gunadarma, 2022)
Insurance sector is an integral part of financial system which offers an important contribution in the nation’s economy. It provides long terms fund for investment which leads to improving financial and non-financial infrastructural facilities. The financial performance of insurance firms, therefore, is an important aspect needing special attention. The paper’s objective is to investigate the impact of micro and macroeconomic indicators on the financial performance of life insurance firms. Based on the Indonesia Financial Service Authority (IFAS) database, a set sample of 30 life insurance firms for the periods of 2011-2018 was generated. Panel data regression analysis was performed to test the formulated hypotheses. Random effect model was identified as the appropriate model indicating that differences in the characteristics between the studied life insurance firms have an effect on the dependent variable, in this case the return on equity. Based on the resulted model, it is revealed that the financial performance i.e. return of equity is affected consecutively by economic growth, expense ratio and current ratio in different direction and magnitudes.